Biomineralized diamond-like carbon films with incorporated titanium dioxide nanoparticles improved bioactivity properties and reduced biofilm formation - Lopes, F. S.; Oliveira, J. R. [UNESP]; Milani, J.; Oliveira, L. D. [UNESP]; Machado, J. P.B.; Trava-Airoldi, V. J.; Lobo, A. O.; Marciano, F. R. (Elsevier, 2017)
Recently, the development of coatings to protect biomedical alloys from oxidation, passivation and to reduce the ability for a bacterial biofilm to form after implantation has emerged. Diamond-like carbon films are commonly used for implanted medical due to their physical and chemical characteristics, showing good interactions with the biological environment. However, these properties can be significantly improved when titanium dioxide nanoparticles are included, especially to enhance the bactericidal properties of the films. So far, the deposition of hydroxyapatite on the film surface has been studied in order to improve biocompatibility and bioactive behavior. Herein, we developed a new route to obtain a homogeneous and crystalline apatite coating on diamond-like carbon films grown on 304 biomedical stainless steel and evaluated its antibacterial effect. For this purpose, films containing two different concentrations of titanium dioxide (0.1 and 0.3 g/L) were obtained by chemical vapor deposition. To obtain the apatite layer, the samples were soaked in simulated body fluid solution for up to 21 days. The antibacterial activity of the films was evaluated by bacterial eradication tests using Staphylococcus aureus biofilm. Scanning electron microscopy, X-ray diffraction, Raman scattering spectroscopy, and goniometry showed that homogeneous, crystalline, and hydrophilic apatite films were formed independently of the titanium dioxide concentration. Interestingly, the diamond-like films containing titanium dioxide and hydroxyapatite reduced the biofilm formation compared to controls. A synergism between hydroxyapatite and titanium dioxide that provided an antimicrobial effect against opportunistic pathogens was clearly observed.
Keywords: Antibacterial activity; Biomineralization; Diamond-like carbon; Hydroxyapatite; Nanoparticles; Titanium dioxide